2011
DOI: 10.1039/c1cc13665h
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of (−)-nakadomarin A

Abstract: A highly diastereoselective bifunctional organocatalyst controlled Michael addition, a nitro-Mannich/lactamization cascade, a furan N-acyliminium cyclisation, a sequential alkyne RCM/syn-reduction and an alkene RCM has allowed a 19 step, highly stereoselective synthesis of (-)-nakadomarin A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(24 citation statements)
references
References 51 publications
0
23
0
1
Order By: Relevance
“…Exposure of this compound to mildly acidic conditions at higher temperature prompted the sterically more hindered hydroxy group at C21 to engage in the necessary second cyclization event. The integrity of ketal 139 thus formed was confirmed by X-ray diffraction before this product was elaborated into the target compound spirastrellolide F (140). [164]…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…Exposure of this compound to mildly acidic conditions at higher temperature prompted the sterically more hindered hydroxy group at C21 to engage in the necessary second cyclization event. The integrity of ketal 139 thus formed was confirmed by X-ray diffraction before this product was elaborated into the target compound spirastrellolide F (140). [164]…”
Section: Methodsmentioning
confidence: 91%
“…Complex 1 a was also used by Dixon and co-workers in their RCAM-based route to nakadomarin A reported shortly thereafter. [140] The elaborate substrate 102 was cyclized in 69 % yield and the resulting pentacyclic product 103 swiftly elaborated to the target by annulation of the still missing eight-membered E ring. In a slightly different setting, the Dixon research group reported yet another approach involving the use of diyne 104 as the substrate, in which the E ring had already been set.…”
Section: Methodsmentioning
confidence: 99%
“…1 The product β-nitroamines have emerged as flexible synthetic building blocks due to the complimentary oxidation states of the two nitrogen atoms. They have been used in the synthesis of many nitrogen containing functional groups including α-amino carbonyls, 2, 3 1,2-diamines, [4][5][6][7] peptidomimetics, 8 natural products [9][10][11][12][13][14][15] and many heterocyclic small molecules. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] To address the paucity of structurally diverse nitroalkanes we have developed conjugate addition nitro-Mannich protocols (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Finally RCM was adapted on the compound to get the desired material 1 in good yield, but with a mixture of Z and E isomer in 63:37 ratio. This problem: in the formation of Z ‐isomer exclusively, was solved by using alkyne during metathesis reaction. Till 2013, their approach attracted the attention of synthetic organic chemists for efficient construction of ABCDE ring in very few steps, highlighting the cascade reaction and enantioselective cojugate adiition reaction.…”
Section: Synthetic Approaches For the Total Synthesismentioning
confidence: 99%